EFEKTIVITAS TEKNIK FLIPPED CLASSROM DALAM MENGOPTIMALKAN PENGUASAAN KONSEP PADA MATERI KONSEP DASAR ILMU EKONOMI - Savaroza, Ayu Isnaeni (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This research aims to evaluate the effectiveness of the flipped classroom technique in improving mastery of basic economic concepts in class X students at SMAN 1 Bonai Darussalam. The study used an experimental design with a pre-test and post-test approach, involving 20 students divided into experimental and control groups. The experimental group was taught using a flipped classroom, while the control group was taught using conventional teaching methods. The research instrument tesa questionnaire and its mastery of economic concepts and results of data analysis using the Independent Samples t-test-test showed that there was a statistically significant difference between the two groups, with a higher average value of concept mastery in the flipped classroom group (16.4000) compared to the control group (-0.6000). The higher standard deviation in the flipped classroom group shows variation in student results, but overall, this technique is more effective in improving concept understanding than conventional methods. In conclusion, the flipped classroom provides a more interactive and productive approach, helping students learn independently and increasing engagement in the learning process. It is recommended that this technique be implemented more widely in teaching economics or other subjects that require a deep understanding of concepts.